How Arterial Embolization Is Transforming Treatment of Oncologic and Degenerative Musculoskeletal Disease - Nicolas Papalexis; Giuliano Peta; Michela Carta; Simone Quarchioni; Maddalena Di Carlo; Marco Miceli; Giancarlo Facchini (Current Oncology)
Background: Arterial embolization is a minimally invasive treatment that occludes blood vessels supplying pathological tissue. Developed to control bleeding without surgery, it has evolved over decades and is now applied in musculoskeletal oncology as a preoperative treatment, palliative care, or standalone therapy for select tumors. Recently, its use has expanded globally in treating chronic pain syndromes and osteoarthritis. Materials and Methods: We reviewed the literature on arterial embolization in various musculoskeletal conditions. The focus was on established oncologic indications for primary and metastatic bone or soft tissue tumors, and emerging evidence on degenerative diseases like osteoarthritis, inflammatory musculoskeletal pathology, and intractable pain. Emphasis was placed on leading studies regarding efficacy, complications, and recurrence rates. Discussion: Arterial embolization has progressed from bleeding control to a versatile therapeutic option in musculoskeletal medicine. It offers symptom relief, reduces tumor size, and improves quality of life. Applications include oncologic interventions and management of degenerative and inflammatory conditions. Despite its benefits, variations in complications and recurrence rates highlight the need for standardized protocols and further research. Conclusions: Arterial embolization is a safe and effective minimally invasive tool in the multidisciplinary management of a wide range of musculoskeletal pathologies. Ongoing research is crucial to understand long-term efficacy, optimize protocols, and broaden its applications.